Therapeutic applications and potential mechanisms of acupuncture in migraine: A literature review and perspectives - Chen, Ying; Liu, Yuhan; Song, Yine; Zhao, Shaoru; Li, Bin; Sun, Jingqing; Liu, Lu (Frontiers in Neuroscience, 2022)
Acupuncture is commonly used as a treatment for migraines. Animal studies have suggested that acupuncture can decrease neuropeptides, immune cells, and proinflammatory and excitatory neurotransmitters, which are associated with the pathogenesis of neuroinflammation. In addition, acupuncture participates in the development of peripheral and central sensitization through modulation of the release of neuronal-sensitization-related mediators (brain-derived neurotrophic factor, glutamate), endocannabinoid system, and serotonin system activation. Clinical studies have demonstrated that acupuncture may be a beneficial migraine treatment, particularly in decreasing pain intensity, duration, emotional comorbidity, and days of acute medication intake. However, specific clinical effectiveness has not been substantiated, and the mechanisms underlying its efficacy remain obscure. With the development of biomedical and neuroimaging techniques, the neural mechanism of acupuncture in migraine has gained increasing attention. Neuroimaging studies have indicated that acupuncture may alter the abnormal functional activity and connectivity of the descending pain modulatory system, default mode network, thalamus, frontal-parietal network, occipital-temporal network, and cerebellum. Acupuncture may reduce neuroinflammation, regulate peripheral and central sensitization, and normalize abnormal brain activity, thereby preventing pain signal transmission. To summarize the effects and neural mechanisms of acupuncture in migraine, we performed a systematic review of literature about migraine and acupuncture. We summarized the characteristics of current clinical studies, including the types of participants, study designs, and clinical outcomes. The published findings from basic neuroimaging studies support the hypothesis that acupuncture alters abnormal neuroplasticity and brain activity. The benefits of acupuncture require further investigation through basic and clinical studies.